MK-801 and cognitive functions: Investigating the behavioral effects of a non-competitive NMDA receptor antagonist - Anna Janus; Klaudia Lustyk; Karolina Pytka (Psychopharmacology, 2023)
Rationale MK-801 (dizocilpine) is a non-competitive NMDA receptor antagonist originally explored for anticonvulsant potential. Despite its original purpose, its amnestic properties led to the development of pivotal models of various cognitive impairments widely employed in research and greatly impacting scientific progress. MK-801 offers several advantages; however, it also presents drawbacks, including inducing dose-dependent hyperlocomotion or ambiguous effects on anxiety, which can impact the interpretation of behavioral research results. Objectives The present review attempts to summarize and discuss the effects of MK-801 on different types of memory and cognitive functions in animal studies. Results A plethora of behavioral research suggests that MK-801 can detrimentally impact cognitive functions. The specific effect of this compound is influenced by variables including developmental stage, gender, species, strain, and, crucially, the administered dose. Notably, when considering the undesirable effects of MK-801, doses up to 0.1 mg/kg were found not to induce stereotypy or hyperlocomotion. Conclusion Dizocilpine continues to be of significant importance in preclinical research, facilitating the exploration of various procognitive therapeutic agents. However, given its potential undesirable effects, it is imperative to meticulously determine the appropriate dosages and conduct supplementary evaluations for any undesirable outcomes, which could complicate the interpretation of the findings.

Protease-activated receptor 2 activation induces behavioural changes associated with depression-like behaviour through microglial-independent modulation of inflammatory cytokines - Serge Moudio; Ashleigh Willis; Karolina Pytka; Roua Abulkassim; Ros R. Brett; Jack F. Webster; Christian Wozny; Mark Barbour; Hui-Rong Jiang; David G. Watson; Josie C. van Kralingen; Scott M. MacKenzie; et al. (Psychopharmacology, 2022)
Rationale Major depressive disorder (MDD) is a leading cause of disability worldwide but currently prescribed treatments do not adequately ameliorate the disorder in a significant portion of patients. Hence, a better appreciation of its aetiology may lead to the development of novel therapies. Objectives In the present study, we have built on our previous findings indicating a role for protease-activated receptor-2 (PAR2) in sickness behaviour to determine whether the PAR2 activator, AC264613, induces behavioural changes similar to those observed in depression-like behaviour. Methods AC264613-induced behavioural changes were examined using the open field test (OFT), sucrose preference test (SPT), elevated plus maze (EPM), and novel object recognition test (NOR). Whole-cell patch clamping was used to investigate the effects of PAR2 activation in the lateral habenula with peripheral and central cytokine levels determined using ELISA and quantitative PCR. Results Using a blood–brain barrier (BBB) permeable PAR2 activator, we reveal that AC-264613 (AC) injection leads to reduced locomotor activity and sucrose preference in mice but is without effect in anxiety and memory-related tasks. In addition, we show that AC injection leads to elevated blood sera IL-6 levels and altered cytokine mRNA expression within the brain. However, neither microglia nor peripheral lymphocytes are the source of these altered cytokine profiles. Conclusions These data reveal that PAR2 activation results in behavioural changes often associated with depression-like behaviour and an inflammatory profile that resembles that seen in patients with MDD and therefore PAR2 may be a target for novel antidepressant therapies.

The selective 5-HT1A receptor biased agonists, F15599 and F13714, show antidepressant-like properties after a single administration in the mouse model of unpredictable chronic mild stress - Monika Głuch-Lutwin; Kinga Sałaciak; Alicja Gawalska; Marek Jamrozik; Joanna Sniecikowska; Adrian Newman-Tancredi; Marcin Kołaczkowski; Karolina Pytka (Psychopharmacology, 2021)
Rationale The prevalence of depression is ever-increasing throughout the population. However, available treatments are ineffective in around one-third of patients and there is a need for more effective and safer drugs. Objectives The antidepressant-like and procognitive effects of the “biased agonists” F15599 (also known as NLX-101) which preferentially targets postsynaptic 5-HT 1A receptors and F13714, which targets 5-HT 1A autoreceptors, were investigated in mice. Methods Antidepressant-like properties of the compounds and their effect on cognitive functions were assessed using the forced swim test (FST) and the novel object recognition (NOR), respectively. Next, we induced a depressive-like state by an unpredictable chronic mild stress (UCMS) procedure to test the compounds’ activity in the depression model, followed by measures of sucrose preference, FST, and locomotor activity. Levels of phosphorylated cyclic AMP response element-binding protein (p-CREB) and phosphorylated extracellular signal-regulated kinase (p-ERK1/2) were also determined. Results F15599 reduced immobility time in the FST over a wider dose-range (2 to 16 mg/kg po) than F13714 (2 and 4 mg/kg po), suggesting accentuated antidepressant-like properties in mice. F15599 did not disrupt long-term memory consolidation in the NOR at any dose tested, while F13714 impaired memory formation, notably at higher doses (4–16 mg/kg). In UCMS mice, a single administration of F15599 and F13714 was sufficient to robustly normalize depressive-like behavior in the FST but did not rescue disrupted sucrose preference. Both F15599 and F13714 rescued cortical and hippocampal deficits in p-ERK1/2 levels of UCMS mice but did not influence the p-CREB levels. Conclusions Our studies showed that 5-HT 1A receptor biased agonists such as F13714 and especially F15599, due to its less pronounced side effects, might have potential as fast-acting antidepressants.

Single Administration of HBK-15—a Triple 5-HT1A, 5-HT7, and 5-HT3 Receptor Antagonist—Reverses Depressive-Like Behaviors in Mouse Model of Depression Induced by Corticosterone - Karolina Pytka; Monika Głuch-Lutwin; Magdalena Kotańska; Anna Waszkielewicz; Agnieszka Kij; Maria Walczak (Molecular Neurobiology, 2017)

HBK-14 and HBK-15 with antidepressant-like and/or memory-enhancing properties increase serotonin levels in the hippocampus after chronic treatment in mice - Karolina Pytka; Katarzyna Gawlik; Dorota Pawlica-Gosiewska; Jadwiga Witalis; Anna Waszkielewicz (Metabolic Brain Disease, 2017)

H3 histamine receptor antagonist pitolisant reverses some subchronic disturbances induced by olanzapine in mice - Magdalena Dudek; Kamil Kuder; Marcin Kołaczkowski; Adrian Olczyk; Elżbieta Żmudzka; Aleksandra Rak; Marek Bednarski; Karolina Pytka; Jacek Sapa; Katarzyna Kieć-Kononowicz (Metabolic Brain Disease, 2016)